Effect of pre and post-natal nutrition on the performances of ewes and lambs under semi intensive rearing system - Ahmed, S; Rakib, MRH; Yesmin, M; Ershaduzamman, M (Bangladesh Journal of Livestock Research, 2020)
The study was conducted to know the effect of different levels of pre and post-natal nutrition on the performances of ewes and their lambs until 1 year of age and the profitable slaughter age of lambs under semi intensive system. Twenty eight (28) native Bengal ewes at 7 weeks of gestation were randomly assigned to four groups (T0, T1, T2, T3) and supplemented with a concentrate mixture at 0.0, 1.0, 1.5, 2.0% of their body weight respectively. Ewes were allowed to graze 8 hours daily. Creep mixture (20 g/lamb/day) was provided to lambs from 2 weeks age with an increment of 10 g/lamb/week. After weaning, 20 growing male lambs were selected and reared 01 year of age with concentrate mixture at 1.5% of their body weight and 8 hours grazing irrespective of treatment groups. Parameters like, ewe’s litter size, daily milk yield, post-partum heat and lamb’s birth weight, weaning weight, live weight at 06, 09 and 12 months were recorded. The data were analyzed in an ANOVA with CRD by using SPSS v. 20. The mean differences were tested by DMRT at a probability level of P<0.05. After weaning, the lamb growths were analyzed considering age as fixed factor. Regression correlations among different parameters with different ages were also performed. Significantly higher daily milk yield (P<0.01), weaning weight (P<0.05) and daily weight gain of lamb until weaning (P<0.05) were observed in T2 group. Besides, lambs weight at 06, 09, and 12 months differ significantly (P<0.01) along with corresponding daily weight gain (P<0.05). Lambs daily weight gain did not differ significantly from weaning to 09 months of age but significantly reduced (P<0.05) from 09 to 12months age. Finally, it may be concluded that a concentrate diet containing 20% CP during late pregnancy to lactation should be supplied to obtain maximum performances of ewes and their lambs. Besides, native Bengal lamb would be slaughtered between 06 to 09 months of age to get maximum return. Bang. J. Livs. Res. Vol. 26 (1&2), 2019: P. 43-50